2016
DOI: 10.1177/1010539516667783
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Socioeconomic Status and Dental Caries Experience in Children in Dili, Timor-Leste

Abstract: Timor-Leste is one of the poorest countries in the world. The aim of this article was to investigate the association between socioeconomic status (SES) and dental caries experience in children living in Dili. Four out of 6 Dili subdistricts and 40 schools were randomly selected. Equal numbers of school children from 4 age groups (6-8, 9-11, 12-14, 15-17 years) were invited to participate. Data were gathered via a questionnaire and an oral examination by dental practitioners. In bivariate analysis, decayed, mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…According to our study, caries frequency was more in the upper-middle class (38.14%) followed by the lower-middle class (32.32%). The result of our study are in accordance with the study conducted by Soares et al, 11 which stated that children belonging to low socioeconomic status reported less incidence of dental caries as compared to mid to high socioeconomic status. This may be explained by larger disposable incomes in people belonging to high socioeconomic status, permitting the purchase of food with high sugar content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our study, caries frequency was more in the upper-middle class (38.14%) followed by the lower-middle class (32.32%). The result of our study are in accordance with the study conducted by Soares et al, 11 which stated that children belonging to low socioeconomic status reported less incidence of dental caries as compared to mid to high socioeconomic status. This may be explained by larger disposable incomes in people belonging to high socioeconomic status, permitting the purchase of food with high sugar content.…”
Section: Discussionsupporting
confidence: 92%
“…Low dental caries among upper-class children is because of better oral hygiene, regular dental visits, oral health knowledge, and positive attitude toward availing oral healthcare services. 11 …”
Section: Discussionmentioning
confidence: 99%
“…However, previous study [34] showed a higher prevalence of dental in children in the high and middle socio-economic class, which may be related to high sugar intake. We found no correlation between caries and socio-economic status, which might be due to the fact that the caries process is multi-factorial.…”
Section: Discussionmentioning
confidence: 88%
“…A recent systematic review has shown that a low socioeconomic level is significantly associated with high risk of tooth decay [10]. On the other hand, a study assessing dental health in 6-17-year-olds revealed that tooth decay was more frequent in children with a moderate-high socioeconomic level [11]. Although the influence of number of demographic factors has been considered, such as the children's age, gender, or place of residence, the findings are noticeably contradictory [12].…”
Section: Introductionmentioning
confidence: 99%